Bem-estar manipulado: o papel mediador do bem-estar percebido na relação entre os estímulos de marketing e a tomada de decisão alimentar - Barros, José Eduardo de Melo (2023)
Food decision making is considerably susceptible to heuristics and marketing stimuli. Consumers infer the overall health level of a food from limited front-of-package claims. At the same time, they infer less flavor in foods considered healthy. Furthermore, brand trust endorses the health appeal of a food and the price level works as a relative health value. Marketing strategies explore factors to influence food decisions, which have repercussions on consumers' well-being. One of the ways of understanding food-related well-being is perceived well-being, which is based on consumer expectations, especially of health and pleasure, and assumes a mediating role in food decisions because it is influenced by marketing stimuli and impacts on consumer responses. Grounded in the Stimulus-Organism-Response (S-O-R) theoretical framework, this thesis argued that marketing mix stimuli, specifically front-of- package claims, sales channel credibility, and price presentation framing, impact on consumer perceptions of health and pleasure and the perceived well-being of consumers, and perceived well-being assumes a mediating role on the effect of stimuli on the decision-making of these consumers. To support this argument, four studies (n = 507) with experimental designs mainly revealed that: 1) the presence (versus absence) of front-of-package claims influences the well-being received, but this influence is necessarily mediated by the perception of health; 2) the presence (versus absence) of front-of-package claims impacts the intention to purchase a food, and again, the sequential mechanism of health perception influencing perceived well- being was observed, generated in the increase of purchase intention; 3) the presence (versus absence) of front-of-package claims interact with the perceived credibility of a retailer brand, increasing the health perception of a product, but only when the retailer has low perceived credibility; and, finally, 4) price presentation framing with the presence (versus absence) of a reference product with increased premium price, mediated by perceived well-being, the intention to purchase the product, and also increased probability of choice according to the well-being goal. In general, the results showed that marketing stimuli can increase as an indication of consumers' health, even when there is no nutritional gain with the products, and consumers' perceived well-being can be envied in contexts whose marketing stimuli favor the these types of heuristics, reverberating in their food responses. The results of this thesis led to the field of food-related well-being, exploring two gaps related to the influence of health and pleasure indications on perceived well-being and the mediating role of perceived well-being in the S-O-R theoretical framework. Managerial and social implications for the retail environment and for products were suggested for the activities of marketing managers and public policy makers interested in the well-being of consumers.